Complementarities between social protection and health sector policies: Evidence from the Productive Safety Net Program in Ethiopia - Hirvonen, Kalle; Bossuyt, Anne; Pigois, Remy (International Food Policy Research Institute, 2017)
Social protection policies typically involve multiple sectors, ranging from food security to health care. Despite this, limited research is directed toward understanding how different social protection programs complement each other. In this study, we explore complementarities between three major national social protection programs in rural Ethiopia: the Productive Safety Net Programme (PSNP), the Health Fee Waiver (HFW) system, and the Community Based Health Insurance (CBHI) in the Ethiopian highlands (Amhara, Oromia, SNNP, and Tigray regions).